2023
DOI: 10.1538/expanim.22-0125
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of amyloid enhancing factor initiates <i>in situ</i> amyloid A deposition followed by systemic lesions in mice

Abstract: Amyloid A (AA) amyloidosis is experimentally transmissible in some animal species, such as mice and chickens. While the spleen is important as the initial deposition site in the transmission of AA amyloidosis, it is not essential for establishing the transmission, and its role is not precisely understood. In this study, to clarify why the spleen is the first site of deposition in transmissible AA amyloidosis, we administered amyloid enhancing factor, which is AA fibrils extracted from AA amyloidosis affected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, four cases developed AFib and AA deposits in the glomeruli and tubular interstitium, respectively (double amyloidosis). In rodents, such as mice [35] and guinea pigs [36], AA deposition is more prominent in the tubular interstitium than in the glomeruli. In the present study, AA depositions were also found in the tubulointerstitium but not in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, four cases developed AFib and AA deposits in the glomeruli and tubular interstitium, respectively (double amyloidosis). In rodents, such as mice [35] and guinea pigs [36], AA deposition is more prominent in the tubular interstitium than in the glomeruli. In the present study, AA depositions were also found in the tubulointerstitium but not in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…White means no peptides were detected. The maximum numbers of detected peptides in each Japanese squirrel (shown in red) were23,23, 42,11, 58,31, 94,32,28,28,28,19,35,28,31,32, and 22, respectively. There were no C-terminal peptides detected after Glu567 in any of the cases.…”
mentioning
confidence: 99%
“…There were no amyloid deposits in Experiment 4 despite intravenous administration of SF in ethanol to mice; therefore, we considered the possibility of amyloid deposits occurring through direct splenic administration, which is more conducive to amyloid deposition [20]. No amyloid deposition was observed in any of the groups.…”
Section: Experiments 5: Intrasplenic Injection Of Incubated Sf In Eth...mentioning
confidence: 93%